KERAGAAN AGROINDUSTRI TEMPE ANGGOTA PRIMKOPTI KABUPATEN PESAWARAN - Tiara Shinta Anggraeni; Dyah Aring Hepiana Lestari; Yaktiworo Indriani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The purpose of this research are to find out: the procurement process of raw materials to meet the six components (precise on time, place, quality, quantity, type, and price), the income and added value of tempeh agroindustry, the marketing mix in the marketing activities of tempeh product, and the supporting services’s role to tempeh agroindustry.  This research is a survey method conducted at purposively  chosen Primkopti in Pesawaran District by consideration that Primkopti was active in business unit and annual member meetings.  The total respondents were 52 respondents selected by random and data were collected in November – Desember 2016.  The data were analyzed using qualitative descriptive analysis and quantitative descriptive analysis.  The results showed that the raw material procurement at the tempeh agroindustry did not meet components of time, place, type, quality, quantity, and price.  The income based on total cost per month at tempeh agroindustry was Rp634,831.56.   Tempeh Agroindustry was viable because it had possitive added value and favorable for its R/C  value was more than one.   Tempeh agroindustry marketing strategy already used marketing mix (product, price, place, promotion).   The marketing chain consisted of two tracts which were, manufacturers to consumers and manufacturers to merchant then to consumers.  The marketing system at tempeh agroindustry was not efficient because the profit margin ratio did not spread evenly.  The support services at tempeh agroindustry were information and communication technology, transportation, and market.Key words: agroindustry, cooperative, performance, tempeh